FHIR based System for Managing Physiological Parameters of Brain Dead Patients - V. , Asha; Jose Chalissery, Benita (International Journal of Psychosocial Rehabilitation, 2020)
Considering the scarcity of human organs for transplantation, it is important to make sure that every available organ is transplanted without wasting it. It gives a better life to someone who is waiting for it. Organs from brain-dead patients are a major source of organs. So, it is important to monitor and maintain the health of the organ of a brain-dead patient while his heart is still beating. A centralized system to monitor and alert about the health of the organ is the best-suited solution to make sure the organ is well kept till it is transplanted. This paper gives an approach based on Health Level 7 Fast Healthcare Interoperability Resources (HL7 FHIR) for such a system, which is centralized and uses new-age technologies to make sure physiological parameters of organs from brain-dead patients are monitored automatically and alerts are provided to the caregivers in case there is any deviation of the monitored parameters.